2011
DOI: 10.1007/s10903-011-9460-y
|View full text |Cite
|
Sign up to set email alerts
|

Rising Disparities in Severe Adverse Birth Outcomes Among Haitians in Québec, Canada, 1981–2006

Abstract: Perinatal health data for Haitians are scant. We evaluated adverse birth outcomes for Haitians in Québec, Canada. We analyzed 2,124,909 live births from 1981 to 2006. Haitian ethnicity was assessed using maternal birth country (Haiti, other Caribbean country, other foreign country, Canada) and home language (Creole, French/English but Creole mother tongue, French/English, other). Associations between ethnicity and preterm birth (PTB), low birth weight (LBW), and small-for-gestational-age (SGA) birth were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…For example, prenatal care use, socioeconomic factors, and geographic location explain most of the disparities in LBW and PTB birth between children of African and European ancestries in Brazil (Nyarko et al, 2013). Disparities in infant health outcomes by ancestry have also been reported in other settings such as between European and non-European ancestries in Italy (Chiavarini et al, 2012) and between different European ancestries in Canada (Auger et al, 2012). …”
Section: Introductionmentioning
confidence: 71%
“…For example, prenatal care use, socioeconomic factors, and geographic location explain most of the disparities in LBW and PTB birth between children of African and European ancestries in Brazil (Nyarko et al, 2013). Disparities in infant health outcomes by ancestry have also been reported in other settings such as between European and non-European ancestries in Italy (Chiavarini et al, 2012) and between different European ancestries in Canada (Auger et al, 2012). …”
Section: Introductionmentioning
confidence: 71%
“…[32][33][34] Research conducted outside the US has tended to focus more on differences by maternal country of birth as opposed to race or ethnicity, with consistently higher preterm birth risks reported among women born in sub-Saharan Africa and the Caribbean than among women born in France, Canada or the Netherlands. 13,15,35 In the US, foreign-born black women have considerably lower preterm birth risk than native-born black women, 17,36 but it is not known whether this pattern holds in other countries. We detected no advantage in preterm birth risk among foreign-born versus native-born black women in Canada, with our results instead suggesting higher preterm and very preterm birth risk among foreign-born black women than among native-born black women in Canada (preterm birth rate 9.2% v. 8.3%; very preterm birth 2.1% v. 1.4%).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that African-born and Caribbean-born women in the provinces of Quebec and Ontario have higher rates of preterm birth than Canadianborn women. [13][14][15] Although the magnitude of these differences is smaller than the disparity in preterm births between black and white women in the US, 16 foreign-born black women in the US have been found to be at lower risk of preterm birth than US-born black women. 17,18 In both Canada and the US, socioeconomic conditions at both individual and neighbourhood levels are important predictors of preterm birth.…”
mentioning
confidence: 93%
“…While the percentage of low birth weight babies was lower among women in our study (5.3), the proportion of preterm pregnancies (11.8%) was slightly higher than CDC surveillance data. Hispanic immigrants born outside the U.S. have a lower risk for preterm low birth rate than non-Hispanic whites [33], though U.S.-born Hispanics have a similar or greater risk compared to non-Hispanic whites [34], which some suggest could be attributable in part to occupational hazards, including repetitive motion, physically demanding and uncomfortable body postures [32]. In our study, we observed no low birth weight deliveries and only one preterm delivery in Haitian women.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research focused specifically on Haitian immigrant women is very limited. One study of 31,663 Haitian-born women residing in Quebec shows that during a 25-year period (1981–2006), 8.5% had pre-term birth and 7.3% had low birth weight infants [33]. While results demonstrated significant, yet surprising differences in employer notification of pregnancy, entry into prenatal care, maternal health symptoms and the self-report of chronic health conditions in children between Haitian and Mexican farmworker women, there is no recent literature on the differences between these two ethnic groups.…”
Section: Discussionmentioning
confidence: 99%